Kajian Daya Dukung Lingkungan dalam Pemanfaatan Ruang di Kawasan Bandung Utara - Putraarta Samodro; Mudiyati Rahmatunnisa; Cipta Endyana (Jurnal Wilayah dan Lingkungan, 2020)
Northern Bandung Area (KBU) plays a vital role and function to surrounding areas as a groundwater catchment area. The West Java Province Spatial Plan (RTRW) stipulates KBU as the Provincial Strategic Area (KSP) for environmental protection. The spatial control governance over the KBU is currently regulated by the Governor Regulation Number 2 Year 2016 about Guidelines for Controling the Northern Bandung Area as the the West Java Province Strategic Area. The KBU development ought to take environmental carrying capacity into account concerning the completion of environmentally based spatial use programs in the KBU. This study aimed to analyze the environmental carrying capacity of land use, and to formulate program recommendation of desired spatial use in KBU. Conservation index method was used to analyze environmental carrying capacity necessary to spatial use program recommendation. The results showed that the land use coverage in 2015 decreased actual conservation function, creating an increase of critical conservation areas by 68.37% and by 69.78% in 2018. In contrast, the conservation index on the land use plan in the RTRW showed a decrease in critical conservation area to 35.90% in 2029. However, such a declining figure has not been supported by environmental programs in the land use plan implementation required to increase the good conservation class by 42.27% while it recorded by 10.78% in 2018. It can be concluded that the IKA and IKC studies showed a distribution expansion of critical lands in KBU, and the IKR analysis proved that the land use plan in the RTRW would reduce critical conservation areas.